2016
DOI: 10.1007/5584_2016_214
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Extracellular Cytokines in A549 Cells and THP1 Cells Exposed to Cigarette Smoke

Abstract: Cigarette smoke (CS) activates inflammatory cells and increases cytokine levels producing local and systemic inflammation. To assess changes in intracellular and extracellular cytokine levels we used human epithelial (A549 cells) and monocyte (THP-1) cell lines grown for 24 h in cigarette smoke-conditioned media. Cytokines were assessed using immunostaining/flow cytometry and ELISA assay. In THP1cells, grown in CS-conditioned media, the intracellular interleukins IL-1β, IL-6, and IL-10 increased by more than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
5
7
0
1
Order By: Relevance
“…1). Although this seems counterintuitive, given the strong association between smoking and lung disease, it is consistent with other studies that have found that cigarette smoke extract is strongly inflammatory only in the human A549 adenocarcinoma cell line but not in primary lung epithelial cells (13,15,46). This data is also consistent with recent data from our laboratory showing a twofold increase in IL-8 production in primary SAEC exposed to dung biomass smoke (25).…”
Section: Discussionsupporting
confidence: 92%
“…1). Although this seems counterintuitive, given the strong association between smoking and lung disease, it is consistent with other studies that have found that cigarette smoke extract is strongly inflammatory only in the human A549 adenocarcinoma cell line but not in primary lung epithelial cells (13,15,46). This data is also consistent with recent data from our laboratory showing a twofold increase in IL-8 production in primary SAEC exposed to dung biomass smoke (25).…”
Section: Discussionsupporting
confidence: 92%
“…A correlation analysis revealed that IL-2, IL-5, IL-10, MDC, insulin, leptin, ACTH, Necropsobacter , and Actinobacillus were associated within the same network. Previous work has identified IL-2, IL-5, IL-10, and MDC to be modulated by smoking [ 74 , 75 , 76 , 77 , 78 ]. Among them, IL-2 is the only cytokine that increased in the smoker group when compared to nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Raw gene count matrix for bulk RNA-seq was downloaded from GEO (accession number GSE147507) (62). The data contained gene expression count matrix of two lung carcinoma cell lines A549 (63,64) and Calu3 (65,66…”
Section: Data Collectionmentioning
confidence: 99%